Michael Handelsman: lector de Benjamín Carrión (Tributo) - Serrano Sánchez, Raúl Eduardo (2019)
This text examines the critical approaches and perspectives developed by American scholar Michael Handelsman with respect to the works and thought of Ecuadorian critic and essayist Benjamín Carrión, one of the most outstanding hermeneutists in the Generation of the Thirties and the Guayaquil Group in Ecuador during the past century. Handelsman has performed a broad and exhaustive study of Carrión’s works, including his vast and complex correspondence, without leaving aside the correct critical assumptions and statements that said works, as Carrión’s thought and political action, demand.